Pembinaan Karakter Kepemimpinan Generasi Muda pada Karang Taruna Desa Kadipaten Kecamatan Andong Kabupaten Boyolali - Viki Bayu Mahendra; Edy Muslimin; Faris Muhana Hidayat; Muhammad Ikhsan Aminudin (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2025)
The young generation has a strategic role in social development, especially in strengthening leadership values and national character. However, in this modern era many young people have experienced a decline in the spirit of mutual cooperation, social care, and responsibility for the community environment. Based on these conditions, this community service activity was carried out with the aim of fostering the leadership character of the younger generation through the Karang Taruna organisation in Kadipaten Village, Andong District, Boyolali Regency. The activity methods used include interactive lectures, group discussions, leadership simulations, and value reflections with a participatory approach. This activity was attended by 25 Karang Taruna members and was held for two days. Evaluation was conducted through observation, questionnaires, and interviews to measure the improvement of participants' understanding, attitudes, and leadership behaviour. The results of the activities showed a significant increase in the participants' understanding of leadership concepts, communication skills, teamwork, and sense of social responsibility. Participants also began to show initiative in designing and implementing social programmes in the village. In addition, this activity strengthens the role of Karang Taruna as a forum for character and leadership development at the village level. In conclusion, leadership character development through educative and participatory approaches has proven to be effective in developing youth leadership with integrity, visionary, and orientated towards social values. This activity is expected to be a model of youth capacity building that can be replicated in other villages.